The Effect Of Pictionary Game Toward Student’s Vocabulary Mastery In Mental Lexicon - Sry Jumartini; Andi Sadapotto; Usman M; Ibrahim Manda; Sam Hermansyah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of this study was to determine whether is pictionary game can impove the student’s vocabulary mastery. This study use quantitative research. The population of this study was seventh grade students of SMPN 1 Pinrang. The total population is 38 students consisting of 2 classes. Class VII1 and VII2 was taken as a sample using random sampling techniques, the total number of samples was 19. The instruments used in this study were vocabulary tests. The results of this study indicate that the pre-test got an average score (41.57) while the post-test got an average score (75.26). This shows that there is a significant difference between the pre-test and post-test. The p-value (0,000) is lower than the significant level (alpha (α) = 0.05). This means H1 is accepted. This study concluded that vocabulary teaching using the four-card game improved students' ability to master vocabulary mastery in seventh grade students of SMPN 1 Pinrang.